Functional interactions between NADPH oxidase 5 and actin - Richter, Samantha M.; Massman, Lilyanna C.; Stuehr, Dennis J.; Sweeny, Elizabeth A. (Frontiers in Cell and Developmental Biology, 2023)
NADPH oxidase 5 (NOX5) is a transmembrane oxidative signaling enzyme which produces superoxide in response to intracellular calcium flux. Increasing evidence indicates that NOX5 is involved in a variety of physiological processes as well as human disease, however, details of NOX5 signaling pathways and targets of NOX5 mediated oxidative modifications remain poorly resolved. Actin dynamics have previously been shown to be modulated by oxidative modification, however, a direct connection to NOX5 expression and activity has not been fully explored. Here we show that NOX5 and actin interact in the cell, and each modulate the activity of the other. Using actin effector molecules jasplakinolide, cytochalasin D and latrunculin A, we show that changes in actin dynamics affect NOX5 superoxide production. In tandem, NOX5 oxidatively modifies actin, and shifts the ratio of filamentous to monomeric actin. Finally, we show that knockdown of NOX5 in the pancreatic cancer cell line PSN-1 impairs cell migration. Together our findings indicate an important link between actin dynamics and oxidative signaling through NOX5.